2023
DOI: 10.1057/s41599-023-02019-9
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of children with gender and sexual minority parents: a review and future directions

Abstract: This article reviews the literature between 2015 and 2022 on mental health disparities between children with gender and sexual minority parents and children with different-sex parents. Although most studies indicate that children with gender and sexual minority parents do not experience more mental health problems than children with different-sex parents, the results are mixed and depend on the underlying sample. The review highlights important shortcomings that characterize this literature, including cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Despite experiencing stigma and discrimination when raising children, same-sex parents may have unique protective factors that buffer against these negative effects of minority stressors. For instance, previous studies showed that same-sex parents may receive social support from the LGBTQ+ community during the transition to parenthood ( Leal et al, 2021 ) and their children generally do well on various outcomes, such as school, mental health, labor, and behavioral outcomes ( Mazrekaj et al, 2020 , 2022 ; Mazrekaj & Jin, 2023 ; Palmaccio et al, 2023 ). The additional support may help same-sex parents cope with those unique minority stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite experiencing stigma and discrimination when raising children, same-sex parents may have unique protective factors that buffer against these negative effects of minority stressors. For instance, previous studies showed that same-sex parents may receive social support from the LGBTQ+ community during the transition to parenthood ( Leal et al, 2021 ) and their children generally do well on various outcomes, such as school, mental health, labor, and behavioral outcomes ( Mazrekaj et al, 2020 , 2022 ; Mazrekaj & Jin, 2023 ; Palmaccio et al, 2023 ). The additional support may help same-sex parents cope with those unique minority stressors.…”
Section: Discussionmentioning
confidence: 99%